Feto-Maternal Outcome in Preeclampsia in Tertiary Care Hospital - Saima Ali, Aneela Habib, Marvi Bozdar, Komal Memon, Aruna Kumari, Sarha Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Despite medical advances, eclampsia and pre-eclampsia remain the foremost reasons of maternal morbidity and mortality worldwide. It can lead to a host of life-threatening complications such as pre-eclampsia, cerebral haemorrhage, eclampsia, liver failure, cardiovascular complications, pulmonary edema, acute renal failure, retinal detachment, HELLP syndrome, hypoxic brain injury, cortical blindness and even maternal death. Objective: To govern the incidence of adverse feto-maternal outcomes in females with preeclampsia. Study Design: Descriptive Case Series. Setting: Department of Obstetrics and Gynaecology, Civil Hospital, Karachi. Duration of Study: This study was held from 10th March 2019 to 10th September 2019. Subjects and Methods: 212 total patients with preeclampsia were involved in the analysis. All women were followed up until delivery and adverse feto-maternal outcomes (HELLP syndrome, Eclampsia, Abruptio placentae, Cesarean Section, Post-partum Hemorrhage, Preterm birth, Birth asphyxia, Low birth weight and perinatal mortality) was noted as per operational definition. Results: Age range in this analysis was from 18 to 35 years with 29.004±2.38 years mean age, 29.641±2.73 weeks was the mean gestational age, mean parity 1.448±1.28 and mean weight was 67.768±5.55 Kg. HELLP syndrome was seen in 30.2% patients, eclampsia 9.9%, abruptio placentae 9.9%, cesarean section 56.6%, PPH 16.5%, preterm birth 28.8%, birth asphyxia 19.3%, low birth weight 21.2% and perinatal mortality was 5.7%. Conclusion: Accessible health education and medical care, and awareness of prenatal control for all women will help in the primary recognition of severe pre-eclampsia.